The Influence of E-Service Quality, Online Promotion, and E-WOM on Purchase Decisions for Aerostreet Shoes on Shopee - Sigit Dwi Saputra; Audita Nuvriasari (Arthatama: Journal of Business Management and Accounting, 2025)
The rapid growth of electronic commerce has transformed consumer purchasing behavior, particularly among Generation Z, who actively engage with online marketplaces like Shopee. This study aims to examine the influence of electronic service quality, online promotion, and electronic word of mouth on the online purchase decisions of Aerostreet shoes on Shopee among Generation Z consumers. A quantitative approach was employed, utilizing primary data collected through questionnaires and secondary data from market reports. The study used a saturated sampling technique, involving 100 respondents, and applied multiple linear regression analysis, validity tests, reliability tests, classical assumption tests, and hypothesis testing. The findings indicate that electronic service quality and online promotion have a positive and significant impact on online purchase decisions, enhancing consumer trust and product visibility. In contrast, electronic word of mouth does not significantly influence purchase decisions, suggesting limited reliance on online reviews. These results underscore the importance of optimizing platform functionality and promotional strategies to attract Generation Z, providing valuable insights for fashion retailers to strengthen their digital marketing efforts on Shopee.